Scottish Common Sense Philosophy: Twelve Theses - McDermid, Douglas (Diciottesimo Secolo, 2025)
What was Scottish common sense philosophy? Understood in purely historical terms, this question is easily answered: it was a school of thought which came into being during the middle third of the 18th century, and which formed a vital part of that many-sided whole now known as the Scottish Enlightenment. But what was its philosophical content? Answering this question is the raison d’être of the present essay. In what follows, I shall identify twelve theses which are central to the distinctive brand of common-sensism articulated by Reid and Stewart. My modus operandi is simple: after stating each thesis, I shall summarize the principal arguments for it and explain its philosophical significance.